Kreativitas Musik Sudilam sebagai Pedagang Arbanat di Kabupaten Jember - Amrullah, Fauriza Atim (Institut Seni Indonesia (ISI) Surakarta, 2019)
This qualitative research reveals the musical creativity of Sudilam, an arbanat or arumanis seller in Jember Regency, East Java, who peddles merchandise by means of rebab (stringed fiddle instruments). Sudilam creativity is the subject of a problem to be explored more deeply. The concept of creativity in working from Rahayu Supanggah is the basis for analyzing. It is stated that the musical characteristics created in a musician are manifested in the individual process and environment, which is supported by various creative endeavors through the use of facilities and media they have. The study concludes that Sudilam long journey as an arbanat seller by means of a rebab has given birth to musical creativity oriented toward the goal of interaction with buyers. This creativity did not come suddenly, but through several stages and important events that Sudilam had experienced in his life.